Evaluasi Program Bantuan Pangan Non Tunai (BPNT) di Kelurahan Morokrembangan Kecamatan Krembangan Kota Surabaya - Puspitasari, Intan; Retno, Diana Puspita; A, Salsabilla Auliazaki; A, Tiara Nebrisca Valonika (As-Syirkah: Islamic Economic & Financial Journal, 2025)
This research evaluates the implementation of the Non-Cash Food Assistance Program (BPNT) in Morokrembangan Village, Krembangan District, Surabaya City. This research aims to assess the effectiveness, efficiency and impact of the program on the welfare of the poor in urban areas with high population density. Using qualitative methods with interviews and document analysis, the research results show that BPNT has helped increase food security and reduce the economic burden on beneficiaries, despite obstacles such as accessibility, sudden distribution and quality of goods. This research recommends increasing outreach, quality monitoring, more accurate data collection, and regular evaluation to increase program effectiveness. These findings are relevant for improving program implementation in the future, both at the local and national levels.